Green synthesis, characterization, and anticancer activity of hyaluronan/zinc oxide nanocomposites - Namvar, Farideh; Azizi, Susan; Rahman, Heshu Sulaiman; Mohamad, Rosfarizan; Rasedee, Abdullah; Soltani, Mozhgan; Abdul Rahim, Raha (Dove Medical Press, 2016)
The study describes an in situ green biosynthesis of zinc oxide nanocomposite using the seaweed Sargassum muticum water extract and hyaluronan biopolymer. The morphology and optical properties of the hyaluronan/zinc oxide (HA/ZnO) nanocomposite were determined by Fourier transform infrared spectroscopy, X-ray diffraction, field emission scanning electron microscopy, transmission electron microscopy, and ultraviolet–vis analysis. Electron microscopy and X-ray diffraction analysis showed that the zinc oxide nanoparticles were polydispersed with a mean size of 10.2±1.5 nm. The nanoparticles were mostly hexagonal in crystalline form. The HA/ZnO nanocomposite showed the absorption properties in the ultraviolet zone that is ascribed to the band gap of zinc oxide nanocomposite. In the cytotoxicity study, cancer cells, pancreatic adenocarcinoma (PANC-1), ovarian adenocarcinoma (CaOV-3), colonic adenocarcinoma (COLO205), and acute promyelocytic leukemia (HL-60) cells were treated with HA/ZnO nanocomposite. At 72 hours of treatment, the half maximal inhibitory concentration (IC50) value via the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was 10.8±0.3 µg/mL, 15.4±1.2 µg/mL, 12.1±0.9 µg/mL, and 6.25±0.5 µg/mL for the PANC-1, CaOV-3, COLO-205, and HL-60 cells, respectively, showing that the composite is most toxic to the HL-60 cells. On the other hand, HA/ZnO nanocomposite treatment for 72 hours did not cause toxicity to the normal human lung fibroblast (MRC-5) cell line. Using fluorescent dyes and flow cytometry analysis, HA/ZnO nanocomposite caused G2/M cell cycle arrest and stimulated apoptosis-related increase in caspase-3 and -7 activities of the HL-60 cells. Thus, the study shows that the HA/ZnO nanocomposite produced through green synthesis has great potential to be developed into an efficacious therapeutic agent for cancers.